Ectopic spleen mimicking hepatocellular carcinoma in the late post-operative period of bariatric surgery - Falcào de Santana, Marcelo; Menezes Marques, Lucas; Lopes Gibara, Vitor; E. Magalhaes Neto, Galeno; Gustavo De Quadros, Luiz; kaiser Júnior, Roberto Luiz; Gouvíªa Faria, Mikaell Alexandre; Filho, Idiberto Zotarelli (Cellular and Molecular Biology, 2018)
An ectopic spleen occurs with less than 600 cases reported and has a large series of splenectomies less than 0.3%. Its highest prevalence occurs between 20 and 40 years of age, being more frequent in female patients. To present an original case report on the occurrence of ectopic spleen, mimicking hepatocellular carcinoma (HCC) after bariatric surgery. Occurrence of migratory spleen after late bariatric surgery, mimicking an HCC discovered in a routine evaluation. JCA patient, male, 66 years old, previously with sleep apnea, hypertensive and diabetic patients on medication regularly, who weighed 112.8 kg, with a BMI of 43.4 kg / m2. After 2 years of by-pass, a routine evaluation identified hepatobiliary surface on hepatic ultrasound performing MRI imaging suggestive of HCC. The team opted for a new laparoscopy with the possibility of cavity inventory beyond the biopsy of the tumor lesion already identified, to track intra-abdominal metastases and to review anatomy. The operation revealed that the suggestive lesion was subcapsular implanted only in the falciform and hepatic surface in segment amenable to total resection. The anatomopathological results of the lesions were described as congenital splenic cells compatible with ectopic spleen. The emergence of the ectopic spleen after laparoscopic bypass has not been reported so far because it is a non-traumatic surgery. The lesion in question had a benign behavior, with hepatic subcapsular implantation restricted to the falciform ligament, capable of total resection. Patient evolved well following follow up with gastroenterologist.